2012
DOI: 10.1186/1471-2407-12-263
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of TACE combined sorafenib in advanced stages hepatocellullar carcinoma

Abstract: BackgroundThe long-term survival in hepatocellullar carcinoma (HCC) patients after transarterial chemoembolization (TACE) remains dismal due to local and/or regional recurrence as well as distant metastasis. The efficacy of sorafenib in advanced HCC has been demonstrated and brought great hope. Recently, the use of sorafenib in combination with TACE for BCLC stage B and C HCC patients was recommended. However, data on this dual-modality treatment is little, and its advantage over TACE alone has not been addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 19 publications
7
59
2
Order By: Relevance
“…The HR in sorafenib/placebo for overall survival was 1.06 (95%CI: 0.69-1.64; P = 0.790) and they concluded that combination therapy with TACE + sorafenib is not superior to TACE alone [35] . However, our findings are in contrast with those from a recent study assessing the effectiveness of TACE + sorafenib vs TACE in Chinese patients; Qu et al [30] reported a statistically significant improvement in median survival time with the combination therapy when compared to TACE alone (27 mo vs 17 mo, P = 0.001). The primary reason for the positive results observed in the study by Qu et al [30] may be attributed to their larger sample size (90 patients) in their study compared with our study with 43 patients.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The HR in sorafenib/placebo for overall survival was 1.06 (95%CI: 0.69-1.64; P = 0.790) and they concluded that combination therapy with TACE + sorafenib is not superior to TACE alone [35] . However, our findings are in contrast with those from a recent study assessing the effectiveness of TACE + sorafenib vs TACE in Chinese patients; Qu et al [30] reported a statistically significant improvement in median survival time with the combination therapy when compared to TACE alone (27 mo vs 17 mo, P = 0.001). The primary reason for the positive results observed in the study by Qu et al [30] may be attributed to their larger sample size (90 patients) in their study compared with our study with 43 patients.…”
Section: Discussioncontrasting
confidence: 56%
“…Furthermore, the study by Qu et al [30] is limited by a relatively uneven duration of patient follow-up for the compared treatment modalities (25 mo for TACE alone and 46 mo for combination therapy). In contrast, our study has even and longer duration of follow-up (56 mo for TACE alone and 52 mo for combination therapy).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of the (doxorubicin-loaded) spheres with systemic anti-angiogenic therapy has already been reported (9)(10)(11), and several phase II and III trials with oral sunitinib (SATURNE) or sorafenib are under way or completed (12,13). Sunitinib malate (SU11248) is available as an oral formulation from Pfizer (New York, New York) and was approved by the U.S. Food and Drug Administration in 2006 for the treatment of renal cell carcinoma and imatinib-resistant gastrointestinal stromal tumor (14).…”
Section: Introductionmentioning
confidence: 99%
“…In phase Ⅱ studies, sorafenib concomitant with TACE or DEB-TACE was well tolerated and effective in unresectable HCC [148][149][150][151] . Synchronous therapy with sorafenib and TACE has also been retrospectively analyzed: the median overall survival for the combined sorafenib and TACE was 27 mo compared to 17 mo for TACE alone [152] . Several prospective controlled studies have evaluated the efficacy of combination treatment [153][154][155][156][157][158] (Table 2).…”
Section: Sorafenib and Tacementioning
confidence: 99%